The regional market for non-timber forest products - Vuola, Matleena; Bauch, Simone C.; Sills, Erin O. (Desenvolvimento e Meio Ambiente, 2018)
The fate of tropical forests is shaped by their perceived value, which in turn depends on awareness of their benefits. Regional markets for non-timber forest products (NTFPs) could both help rural people generate income from forests and raise urban awareness of forest benefits. We assess the urban market for NTFPs in Belém do Pará, the largest metropolitan area in the Brazilian Amazon, through a survey of consumers in 2006 – 2009. We segmented the urban consumer market in order to explore patterns in consumption and knowledge about NTFPs. We find that the market segments that consume the greatest number of NTFPs were characterized by relatively higher income and education as well as more recent migration to Belém. This suggests that demand for non-timber forest products does not fade with improved socioeconomic status. However, environmental education is needed to convert this demand into recognition of the benefits provided by forests, as many consumers are not aware that the products they consume come from the forest. In the two largest consumer segments, most consumers could not spontaneously list any forest product they consume, even though when a list of NTFPs was presented, many (>75%) indicated that they did consume the two most popular forest products: açaí palm fruit (Euterpe oleraceae) and Brazil nuts (Bertholletia excelsa). Consumers in these largest segments have lower incomes, are more likely to have been born in Belém and are less likely to have completed postsecondary education. In addition to not recognizing that they consume forest products, many of these consumers had no direct experience of the forest: less than half of the survey respondents in these segments reported that they had ever visited the forest, despite living in a city located in the midst of the largest tropical forest in the world.